Comprehensive numerical simulation of an indirect internal reforming tubular SOFC - Nishino, T; Iwai, H; Suzuki, K (2005)
A comprehensive numerical simulation of a cell-based indirect internal reforming tubular Solid Oxide Fuel Cell has been conducted. Two-dimensional axisymmetric thermo-fluid fields and non-axisymmetric electric potential/current fields in the tubular cell were simultaneously solved. As a result, complex interactions between the thermo-fluid and electrical fields were clearly demonstrated. It was also revelated how the thermal field and power generation characteristics of the cell are affected by catalyst density distribution for the reforming in the cell. A linear distribution of the catalyst greatly reduced the maximum temperature and temperature gradients of the cell with little negative impact on the power generation performance of the cell.